Linee guida per la scelta dei trattamenti integrati dell’utente in carico ai Ser.D. - Lamartora, Vincenzo (Mission - Open Access, 2021)
In our study, so-called evidence of efficacy of different treatments used in the addiction clinic is reviewed and discussed. In the first part of the study, the criticisms made of psicoanalytic treatment, accused for many years of not being an evidence-based treatment, are examined and refuted. All types of treatments can be useful for a Service, as long as the Operators are able to carry out a real multidisciplinary diagnosis of the user and send it according to well-established guidelines, to this or that integrated treatment In the second part of the study we highlighted four clinical dimensions to be explored – in the diagnosis phase – and four treatment areas (care settings, pharmacological treatments, socio-occupational rehabilitation and the defensive transformations that the user agrees to face). Combining the four clinical dimensions with the four areas of treatment just mentioned, result in four clusters of users, characterized by increasing severity, each of which has its own clinical and existential characteristics and should be sent to a specific integrated treatment. The difference between confusion and functional organization lies in the presence of “guidelines” that depending on the Overall Representational Structure of the user and the operating models available to the Service may serve to specifically send this or that user to this or that form of psychological therapy.